Distinctiveness Reconsidered: Religiosity, Structural Location, and Understandings of Racial Inequality. Issue 2 (2nd August 2017) - Frost, Jacqui; Edgell, Penny
Abstract : Are conservative Protestants distinct in their support for individualistic explanations of racial inequality in America? Past research has generated contradictory findings on this question, along with debates about the best measure of evangelicalism and the factors that moderate religious influences on racial attitudes. Using data from the nationally representative Boundaries in the American Mosaic Project (2014), we examine how structural location interacts with religious commitment to influence understandings of and preferred solutions to African‐American disadvantage. We show that religious beliefs, involvement, and centrality influence adherents differently, depending on their age, gender, education, income, and race. We find that measures do matter, and that denominational affiliation is less predictive than the orthodoxy and centrality of religious belief. We also find that straightforward talk about distinctiveness can mask the strong and pervasive effects of structural location on racial attitudes. We call for more research that makes the interaction between religiosity and structural location a central focus of analysis.